APLIKASI PENAMBAHAN MULTI ENZYME DALAM RANSUM AYAM RAS PEDAGING - PUTRA WIBAWA WIBAWA; BUDI RAHAYU TANAMA PUTRI; A.A. AYU TRISNADEWI (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2008)
A social service was carried out to improve innovation and technological knowledge on the scope of animal husbandry. This social service applied through two methods as of direct application and agricultural extension. The application was done on 102 broiler chickens at the age of 2 weeks which were divided into three groups within three kinds of treatment: First treatment = mixed feed, Second treatment = mixed feed + 0,2% of multi enzyme, Third treatment = Commercial feed. The results of this economic analysis (IOFCC) showed that utilization of mixed feed + 0,2% multi enzyme could give a higher benefit compared with the utilization of mixed feed without mixed of multi enzyme and commercial feed. The agricultural extension was conducted on 23rd of September 2006. The advantageous of multi enzyme supplementary in feed of broiler chicken was being discussed, and then group discussion was carried out to discuss problems faced by the farmer.